Prevalence Study of the Intestinal Protozoal Parasitic Infections Rates at Babylon and Kerbala Cities - Haddawee, Riyadh Hatim (Journal of Kerbala for Agricultural Sciences, 2024)
Intestinal protozoa are parasites transmitted by the consumption of contaminated water and food and mainly affect children and older people and cause considerable health problems. They are leading to causes of outpatient morbidity in developing countries due to diarrhea. The aim of this study was invetigation the prévalence of Entamoeba histolytica and Giardia lamblia parasites at Kerbala and Babylon cities in 2022. The research was conducted during the period starting from 1/1/2021 until 31/12/2021 in the provinces of Babylon and Kerbala. The Imam Al-Sadiq Hospital in Babylon and the AlHusseini Hospital in Karbala were taken. Data were collected in both hospitals to detect the spread of the disease (E.histolytica) and they were taken. Considering the percentage of injuries for age groups and gender of the injured during the months of the year. Results of this study showed that rates of intestinal parasitic infections at the Hospitals of Babylon City at Imam Sadiq Hospital, while the total infection rates was 6.58% While the total infection rate with the same parasite at Al-Hashimiya Hospital was 29%. At Hospitals of Kerbala city, the total infection rate at Al-Hussein Hospital was 21.37% While the rate of infected people at Al-Husseiniya Hospital was 26.4% The results of infection rates with Giardia lamblia in the current study showed the following:- At hospitals of Babylon city the total infection rate was 14.3% When it reached Imam Sadiq Hospital, the infection rate was 1.72% While the rate of infection in Al-Hashimiya Hospital was: 1.69% At hospitals of Kerbala city the infection rate was in Al-Hussein Hospital 1.83% While the rate of infected people was at Al-Husseiniya Hospital 2.21% The total infection rate was .4..% as the infection rate was in Al-Hussein Hospital 1.83%, while the infection rate in Al-Husseiniyah Hospital was 2.21%.